Framing land expropriation: a comparative content analysis of SABC and eNCA's coverage of the LEWC public hearings - Tshiame, Enica Mogomane (Centre for Film and Media Studies, 2026)
This study examines how eNews Channel Africa (eNCA) and the South African Broadcasting Corporation framed public hearings on amending Section 25 of the Constitution for land expropriation without compensation, a deeply political issue in post- apartheid South Africa. Using thematic content analysis of YouTube news bulletins, the study identifies each channel's framing techniques and dominant themes. Findings reveal that SABC utilised human-interest framing more frequently (42% vs. 23% for eNCA), while eNCA leaned towards economic framing (31% vs. 28% for SABC). The thematic analysis highlights further distinctions: eNCA focused more heavily on social justice (42% vs. 29% for SABC), while SABC emphasised land as a cultural right (20% vs. 12%) and highlighted social injustice more prominently (27% vs. 17%). These variations underline how each channel constructed distinct narratives surrounding land reform, demonstrating the significant influence of media framing on public opinion. This study contributes to broader discussions about media influence, political discourse, and social justice in the context of land reform in South Africa, advocating for balanced reporting that considers the historical context, diverse viewpoints, and potential societal impacts of this sensitive issue.